Measurement of the inclusive differential jet cross section in pp collisions at √s=2.76 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; et al. (Physics letters, 2013)
The ALICE Collaboration at the CERN Large Hadron Collider reports the first measurement of the inclusive differential jet cross section at mid-rapidity in pp collisions at s=2.76 TeV, with integrated luminosity of 13.6 nb−1. Jets are measured over the transverse momentum range 20 to 125 GeV/c and are corrected to the particle level. Calculations based on Next-to-Leading Order perturbative QCD are in good agreement with the measurements. The ratio of inclusive jet cross sections for jet radii R=0.2 and R=0.4 is reported, and is also well reproduced by a Next-to-Leading Order perturbative QCD calculation when hadronization effects are included.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
The ALICE collaboration: B. Abelev, V. Angelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, T. Krawutschke, M.J. Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado-Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, J. Ulrich, S. Vallero, M.A. Völkl, Y. Wang, B. Windelband, A. Zimmermann und weitere 947
Gesehen am 29.04.2021